Krishna life and songs of the blue god - Menon Ramesh (New Delhi Rupa, 2006)
This book is a magical, unexpurgated life of Krishna, told in a spirit of bhakti for the modern reader. It opens on the battlefield of Kurukshetra, on the brink of war, when the Pandava warrior Arjuna suffers a crisis of courage and conscience. His divin
Keywords: Krishna(Hindu deity)